The impact of ESG disclosure and green mining on firm value: evidence from Indonesia - Budi Suharto, Raden Setya; Sanga, Marianus Hendrilensio; Situmorang, Resvina; Handa, Resky Pramudita (Jurnal Mantik, 2025)
This study examines the impact of Environmental, Social, and Governance (ESG) disclosures and the adoption of green mining practices on the value of mining companies in Indonesia. Using a quantitative research method, we analyze panel data from 20 mining companies listed on the Indonesia Stock Exchange (IDX) over the period from 2020 to 2022. The study estimates the relationships between ESG, green mining, and firm value through panel data regression, applying a fixed effects approach. The results show that neither ESG disclosures nor green mining significantly affects firm value, as measured by Tobin's Q. In contrast, firm size negatively impacts value, while ROA has a positive influence. These findings suggest that investors tend to prioritize traditional financial indicators over sustainability factors when evaluating mining companies. The theoretical implications of this study highlight that, although ESG and green mining are conceptually important, their current levels of implementation are insufficient to meaningfully affect market valuations. Practically, mining companies need to improve the transparency and effectiveness of their ESG reporting and strengthen their sustainability strategies to create additional value for investors and other stakeholders